THE FEATURES OF THE INDICATOR MINERALS OF KIMBERLITES IN A NEW PIPE YANVARSKAJA (WESTERN YAKUTIA) - D. V. Ivanov; V. V. Ivanov; A. V. Tolstov (Известия высших учебных заведений: Геология и разведка, 2017)
The first results of the mineral-petrographic studies of microclastes of kimberlites from the basal horizon of the Upper Paleozoic deposits of the Alakit-Markhinsky kimberlite field (Western Yakutia) have been presented. The main features of the indicator minerals of kimberlites (IMK) have been revealed. These minerals are picroilmenite, pyrope, chromspinels, phlogopite, chromdiopside and olivine. The ways of their further studying in connection with the search for kimberlite bodies have been outiined. The opening of the Yanvarskaja pipe has confirmed the correctness of the methodology for testing the basal horizons of the Upper Paleozoic deposits on the core of the wells. Minerals containing rare-earth elements (REE) have been found in the kimberlites of the new tube, which requires further research. The results of the study of the IMK of Yanvarskaja pipe serve as a supplement to the database on the Alakit-Markhinsky field and allow more reliable prediction and identification of new objects, including high-diamond ones.